Determinants of Mobile JKN Application Utilization in Supporting Healthcare Access among Informal Workers at Kenali Besar Primary Health Center, Jambi City, Indonesia - Dina Rosalina; Dwi Noerjoedianto; Andi Subandi; Ummi Kalsum; Herlambang; Muldiasman (Rifa'Institute, 2026)
Introduction: Mobile JKN is a digital innovation developed by BPJS Kesehatan to improve healthcare access for National Health Insurance (JKN) participants. However, its utilization among informal workers remains suboptimal. Objective: This study aimed to analyze the determinants of Mobile JKN utilization in supporting healthcare access among informal workers. Method: A cross-sectional study was conducted among 126 informal workers who were JKN participants in the working area of Kenali Besar Primary Health Center, Jambi City, Indonesia. Respondents were selected using accidental sampling. Data were analyzed using chi-square tests and multiple logistic regression. Results and Discussion: A total of 58.73% of respondents had utilized the Mobile JKN application. Significant associations were found between perceived ease of use (p=0.002), perceived usefulness (p=0.006), behavioral intention (p=0.022), attitude toward use (p<0.001), digital literacy (p=0.038), healthcare service needs (p=0.007), and Mobile JKN utilization. Multivariate analysis identified attitude toward use as the most dominant determinant (aOR=3.19; 95% CI=1.38–7.36; p=0.006). Conclusion: Perceptions and behavioral factors significantly influence Mobile JKN utilization. Improving users' attitudes toward the application may increase its utilization among informal workers